EFFECT OF FLANKING SEQUENCES ON THE ACCURACY OF THE RECOGNITION OF TRANSCRIPTION FACTOR BINDING SITES - T. M. Khlebodarova; D. Yu. Oshchepkov; V. G. Levitsky; O. A. Podkolodnaya; E. V. Ignatieva; E. A. Ananko; I. L. Stepanenko; N. A. Kolchanov (Вавиловский журнал генетики и селекции)
The development of in vitro methods produced new experimental information on protein binding to DNA, which is accumulated in databases and used in studies of mechanisms regulating gene expression and in the development of computer-assisted methods of binding site recognition in pro- and eukaryotic genomes. However, it is still questionable to what extent sequences selected in vitro reflect the actual structures of natural transcription factor (TF) binding sites. The Kullback – Leibler divergence was applied to the comparison of frequency matrices of TF binding sites constructed on samples of artificially selected sequences and natural sites. Core sequences of natural and artificial sites showed high similarity for 80 % of all TFs studied. For 20 % of TFs, binding site sequences selected in vitro had a broader range of permissible significant nucleotides not found in natural sites. The optimum lengths of DNA sequences including natural binding sites, at which they are recognized most accurately, were estimated by the weight matrix method. For approximately 80 % of the TFs studied, the optimum binding site length notably exceeded the lengths of the core sequences, as well as the lengths of in vitro selected sites. The detected features of in vitro selected TF binding sites impose constraints on their use in the development of computer-assisted methods of the recognition of candidate sites in genomic sequences.